8. RESPON PEMERINTAH INDONESIA TERKAIT SEKURITISASI WWF MELALUI KAMPANYE SAVE OUR SHARKS - Saraswati, Widya Kusuma; Susiatiningsih, Hermini; Farabi, Nadia (Journal of International Relations, 2016)
Shark fishing is one of the main profitable commodities for fishermen. Every part of itfrom its head, fin, tail, to the organ inside the body can be sold with high price. Thiscaused the high number of IUU fishing towards shark, even Indonesia was once thecountry with the highest number of shark killing from 2002-2010. WWF has promoted amovement to stop the shark consumption and shark goods production trough Save OurSharks campaign. Based on background, the research question is â€œhow is the responds ofIndonesiaâ€™s government regarding to WWFâ€™s securitization towards Save Our Sharkscampaign?.â€ The purpose of this research is to find out the IUU fishing problem inIndonesia and the responds of Indonesiaâ€™s government regarding the securitization ofWWF trough Save Our Sharks campaign. In answering those purpose, the author usesconstructivism trough securitization theory and state centric constructivism theory. Themethod used is qualitative research with interview and literature review technique. And theresult is; the government responds the campaign trough some policies based on The Sharkand Rays Symposium to overcome the shark problems in Indonesia such as IUU fishing,shark trade, shark conservation, and repairing the shark protection regulation in Indonesia.The results of the symposium are used as the base of the creation of shark protectionregulation in the future. To face the challenge of IUU fishing towards sharks in the future,researcher have some advices to Indonesiaâ€™s government, such as fixing regulations andpolicies related to shark fisheries for more detail and specifically includes physicalcharacteristics, species, quota, capture mechanism, utilization, trade, and sanctions.